RHETORICAL STRUCTURE OF THE JUDGES’ CONSIDERATIONS IN HATE SPEECH CASES - Aisah; Aceng Ruhendi Saifullah; Dadang Sudana (University of Kuningan, 2025)
This study examines the rhetorical structure of judges’ considerations in hate speech cases from a forensic linguistic perspective. While previous research has largely focused on identifying hate speech in digital discourse or on the linguistic features of evidentiary texts, limited attention has been paid to how judges construct legal reasoning in their written decisions. Employing a qualitative genre-based approach integrated with Rhetorical Structure Theory (RST), this study analyzes judicial considerations as an institutional legal genre characterized by patterned argumentative moves. The findings reveal that judges’ considerations are systematically organized through recurring rhetorical stages, including case contextualization, linguistic evaluation of disputed utterances, alignment with statutory norms, argumentative reinforcement, and verdict legitimation. Coherence within judicial reasoning is predominantly achieved through justification, evaluation, and reinforcement relations, which function to present legal conclusions as inevitable and socially necessary. These results demonstrate that judicial reasoning in hate speech cases is not discursively neutral but strategically constructed to establish legal authority and institutional legitimacy. The study contributes to forensic linguistics and legal discourse analysis by foregrounding judges’ considerations as a central site of meaning-making in hate speech adjudication and by offering an analytical framework for examining rhetorical organization in judicial texts.